IDENTIFYING PUBLIC PREFERENCES FOR THE VALUE OF DAILY USED OPEN SPACES USING THE ANALYTIC HIERARCHY PROCESS – A CASE STUDY OF HANGZHOU CITY, CHINA - J. R. Shi; X. M. Zhao; J. Ge; K. Hokao; Z. Wang (International Association of Lowland Technology, 2006)
Although much research exists on whether public open spaces are satisfactory with respect to users‘ perception, designers often neglect residents‘ preferences before a project is to be authorized. Especially when they design daily used open spaces that are located near or inside residential areas, the value of spatial environments is not paid enough attention to. This study applies the Analytic Hierarchy Process (AHP) to a field survey in order to compare the residents‘ perspectives concerning three general attributes (functional, aesthetic and ecological) and ten specific qualities of daily used open spaces. AHP is a methodology that assists respondents to make subtle trade-offs in unquantifiable attributes by means of measuring the relative preference of one attribute over another. Although this methodology is entirely different from other choice-based methods considering the cost-efficiency, the results of AHP offer a systematic method to examine the demands of those unheeded people. The results of the AHP application into data collected from the Chinese residents find that public preferences for daily used open spaces are stronger for the functional attribute, rather than the aesthetic attribute in the ancient Chinese tradition. Furthermore, comparisons of ten specific qualities show that the public prefers the open spaces that can be utilized conveniently and easily for group activities, because such spaces keep an active lifestyle of neighborhood communication, which also is seen to protect human-regarding residential environments.